Pharmacological Treatment of Obesity in Older Adults - Žižka, Ondřej; Haluzík, Martin; Jude, Edward B (Drugs &aging, 2024)
Obesity is a complex health issue with growing prevalence worldwide. It is also becoming more prevalent in the population of older adults (i.e., 65 years of age and older), affecting frequency and severity as well as other comorbidities, quality of life and consequently, life expectancy. In this article we review currently available data on pharmacotherapy of obesity in the population of older adults and its role in obesity management. Even though there is growing evidence, in particular in the general population, of favourable efficacy and safety profiles of glucagon-like peptide-1 (GLP-1) receptor agonists liraglutide and semaglutide, and recently dual GLP-1 and glucose-dependent insulinotropic polypeptide (GIP) agonist tirzepatide, concise guidelines for older adults are not available to this day. We further discuss specific approaches to frequently represented phenotype of obesity in older adults, in particular sarcopenic obesity and rationale when to treat and how. In older adults with obesity there is a need for more drug trials focusing not only on weight loss, but also on geriatric endpoints including muscle mass preservation, bone quality and favourable fat distribution changes to get enough data for evidence-based recommendation on obesity treatment in this growing sub-population.
Keywords: senioři; Glucagon-Like Peptide-1 Receptor Agonists; obezita; sarkopenie; agonisté receptoru pro glukagonu podobný peptid 1; Anti-Obesity Agents; Humans; Obesity; Aged; Sarcopenia; látky proti obezitě; lidé